Recent advances and potential applications of the photo-induced macroscopic response of self-assembled azopolymer in aqueous media - Shen, Wenming (2014)
This mini-review highlights issues related to the photo-triggered macroscopic response of azopolymer in supramolecular hydrogel and polymer vesicles. Cyclodextrin (CD) can form an inclusion complex with trans-azobenzene while cis-azobenzene is expelled out of the CD's cavity. This photo-reversible supramolecular host − guest interaction is used to trigger sol − gel transitions and to induce macroscopic assembly. When substituted azobenzene is located at chain ends of linear polyethylene glycol, monodisperse vesicles are formed exhibiting a photo-induced pulsating behavior. The macroscopic phase transition and assembly or pulsating behavior of azopolymers can be expected to have potential applications as smart biomedical materials.